Kansas Irrigation Leases - O'Brien, Daniel M. (My University, 2001)
This publication illustrates crop-share irrigation lease inputs and costs for center-pivot and flood-irrigation systems.
MF284_2001_10
Keywords: MF284; Livestock; Economics; MF